Social connectedness and engagement in preventive health services: an analysis of data from a prospective cohort study. (September 2018) - Stafford, Mai; von Wagner, Christian; Perman, Sarah; Taylor, Jayne; Kuh, Diana; Sheringham, Jessica
Summary: Background: Evidence of the possible health benefits of social connectedness is increasing. We aimed to examine poor social connectedness as a possible barrier to participation in preventive health services among older people (aged 53–69 years). Methods: We analysed data from a prospective cohort study of 5362 socially stratified births from the Medical Research Council National Survey of Health and Development enrolled in England, Scotland, and Wales in March 1946. At ages 68–69 years, participants reported participation in blood pressure and cholesterol measurement, eyesight and dental check-ups, influenza immunisation, and bowel and breast cancer screening. Our primary outcome measure summed participation across all these tests and services at ages 68–69 years. We tested associations between structural and functional social connectedness from ages 53 years to 69 years and total count of participation in these preventive services in Poisson models controlling for sex, education, occupational class, employment, chronic illnesses, and general practitioner consultations for health problems. Findings: 940 (44%) of 2132 participants attended all preventive services within the recommended timeframes. At ages 68–69 years, being unmarried or not cohabiting (incident rate ratio [IRR] 1·33, 95% CI 1·20–1·47) and small personal social networks (IRR 1·51, 1·32–1·71) were independently associated with non-participation in more services, with associations consistent across most services. High social relationship quality at ages 68–69 years (IRR 0·91, 95% CI 0·87–0·95) and increasing social relationship quality from ages 53 years to 69 years (IRR 0·93, 0·89–0·97) were associated with low risk of non-participation. Interpretation: Individuals with poor social connectedness appear to be at greater risk of not engaging in the full range of preventive services than individuals with good social connectedness. Improvement of access to social contacts and networks in older ages is already recommended for the maintenance of good mental health. This study suggests that social connectedness could also improve participation in a wide range of preventive health services, and hence could improve use of the health-care system and population health. Funding: UK Medical Research Council.